Bench Dip Exercise on Smash Accuracy in Volleyball Athletes - Iyakrus Iyakrus; Silvi Aryanti; Anellia Pranesta (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
In this study, famale volleyball players from the OPBVP Prabumulih club will be evaluated to identify the impact of bench dip training on smash accuracy. A quasi-experiment with a pre test-post test one group design was employed as the methodology. There were 35 participants in the study's sample. The tool is a test of smashing abilities. After receiving therapy for 5 weeks with a frequency of exercise four times per week, it was discovered that the treatment in this study took the form of Bench Dip exercise. Based on study and data analysis findings, it was determined that tcount (15.29) was higher than ttabel(1.69) and that t count > ttabel caused H1 to be approved and H0 to be rejected. Therefore, H1 may be accepted, indicating that striking the ball hanging has an impact on improving the precision of the volleyball smash during practice sessions of the OPBVP Prabumulih club. This study implies that a kind of workout called bench dips may be utilized to increase smash accuracy.